NIR-dye Based Heat Generation System for Studying Thermodynamic Response of Lipid-Bilayers - Xue, Lin (My University, 2019)
In this study, we develop a local heat generation system utilizing the photothermal effect on the micro-scale. Organic dye molecules are hosted in a polymer matrix to construct an NIR-absorbing medium, and it is proved to be an alternative candidate to plasmonic nanoparticles for creating a system with high absorption in the NIR regime and high transmission at visible wavelengths. We carry out optical and thermal simulations to optimize the heat generation of such a system. The transfer matrix method is used to calculate the system absorption dependence on the NIR-absorber thickness and NIR dye concentration. It is shown that for a concentration of 5 mg/ml a 20 m thick absorbing layer can provide 30% of absorption at 1064 nm, which is sufficient for generating an effective heat source density. In COMSOL multiphysics we obtain a simulation of the heat generation system in two configurations, indicating that the illumination with a NIR laser can provide sufficient heating. It is valuable to study the micro-scale thermal migration and manipulation of biological particles in a temperature gradient, since it can provide the information on the interaction between the molecules and the solvent. Therefore, based on our NIR-absorbing system, we present several experiments investigating the thermodynamic response of lipid-bilayers. It is found that the local heating can facilitate the formation of lipid-bilayers from fluidic phase adsorbed vesicles. This might result from the promotion of vesicle rupture and the consequent fusion between lipids leading to the formation of a bilayer. Another study utilizing the lipid phase transition demonstrates that a photobleached spot within a gel phase lipid-bilayer can only recover in the presence of NIR-laser heating causing the local temperature to increase above the transition threshold. Adopted from this observation, we establish a reversible gel phase lipid lithography system, which utilizes a visible laser and NIR laser as a pen and eraser, respectively, to be able to optically print a desired pattern on the canvas made of lipid materials and then thermally remove it.
Keywords: NIR dye; optical absorption; photothermal effect; lipid-bilayers; lipid phase transition